Evolution of the intracratonic Officer Basin, central Australia: implications from subsidence analysis and gravity modelling - Haddad, D; Watts, A; Lindsay, J (2001)
The intracratonic basins of central Australia are distinguished by their large negative Bouguer gravity anomalies, despite the absence of any significant topography. Over the Neoproterozoic to Palaeozoic Officer Basin, the anomalies attain a peak negative amplitude in excess of 150 mGal, amongst the largest of continental anomalies observed on Earth. Using well data from the Officer and Amadeus basins and a data grid of sedimentary thicknesses from the eastern Officer Basin, we have assessed the evolution of these intracratonic basins. One-dimensional backstripping analysis reveals that Officer and Amadeus basin tectonic subsidence was not entirely synchronous. This implies that the basins evolved as discrete geological features once the Centralian Superbasin was dismembered into its constituent basins. Two- and three-dimensional backstripping and gravity modelling suggest that the eastern Officer Basin evolved from a broad continental sag into a region of intracratonic flexural subsidence from the latest Neoproterozoic, when flexure of the lithosphere deepened the northern basin. The results from gravity modelling improve when the crust is thickened beneath the northern margin of the basin and thinned at the southern margin, as has been suggested by recent deep seismic data. The crustal thickening beneath the basin's northern margin abuts the region of greatest topographic relief and is consistent with the observed structure at the edges of many orogenic belts. If the Officer Basin evolved as a foreland-type basin from the late Proterozoic and has retained those features to the present, then one implication is that in the absence of any significant topography, cratonic lithosphere must be able to support stresses over very long periods of geological time.